2019
DOI: 10.1186/s13643-019-1182-6
|View full text |Cite
|
Sign up to set email alerts
|

Defining the concept of family caregiver burden in patients with schizophrenia: a systematic review protocol

Abstract: BackgroundSince the deinstitutionalization policy, in psychiatric hospitals, the care of patients with schizophrenia was left to their families which has been imposing a heavy burden on them. Family caregiver burden could have consequences for caregivers, patients, and the society. There is very little consensus on the definition and dimensions of the caregiver burden, which leads to a lack of consistency in the results of research. Thus, the present study was aimed to redefine the family caregiver burden of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 32 publications
1
26
0
4
Order By: Relevance
“…Because there is a deep-rooted family collectivism in China’s rural areas, when a person is sick, the whole family are likely to unite to take care of the patient [ 24 ]. Some studies have shown that the burden of rural families is negatively correlated with the function of community care network, family members of patients may encounter various difficulties in providing care for patients with mental disorders, and tend to have family caregiver burden [ 24 , 25 ]. The family caregivers’ burden is not only a Chinese issue but a global issue.…”
Section: Discussionmentioning
confidence: 99%
“…Because there is a deep-rooted family collectivism in China’s rural areas, when a person is sick, the whole family are likely to unite to take care of the patient [ 24 ]. Some studies have shown that the burden of rural families is negatively correlated with the function of community care network, family members of patients may encounter various difficulties in providing care for patients with mental disorders, and tend to have family caregiver burden [ 24 , 25 ]. The family caregivers’ burden is not only a Chinese issue but a global issue.…”
Section: Discussionmentioning
confidence: 99%
“…In another study aimed at determining the educational needs of caregivers of patients with schizophrenia, it is stated that they need information about the early signs and symptoms of the illness, the effects of drugs, and coping with the patient's unusual and aggressive behaviors (Bademli et al, 2016;Raghavan et al, 2017). In the study conducted by Tamizi et al (2020), it was similarly reported that the family caregivers mentioned experiences such as lack of knowledge about the nature of the disorder, methods of treatment, how to provide care for the patient at home, insufficient awareness in managing the high-risk behavior of the patient and in dealing with the patient's resistance to treatment. In another study showed that caregivers were unaware of the nature of the illness, treatment schemes, or illness trajectories (Von Kardorff et al, 2016).…”
Section: Meaning Of Schizophreniamentioning
confidence: 99%
“…Caregiver burden refers to the strain endured by a person who cares for a chronically ill individual [ 11 ]. Although there has been much debate in the literature regarding the dimensions and attributions of the construct, a distinction has been made between objective and subjective burden [ 11 ]. Objective burden includes concrete costs to the caregiver, such as time and finances devoted to care.…”
Section: Introductionmentioning
confidence: 99%